Prague Spring: Workers' Control in a State‐Owned Economy. Issue 3 (2nd September 2013) - Dolack, Pete
Abstract : A subtle contradiction arises for a worker in a collectively controlled enterprise because such a worker is simultaneously employee and manager. This duality is particularly noticeable when the enterprise is state‐owned. The workers' control movement during Czechoslovakia's Prague Spring sought to reconcile this duality by creating workers' assemblies that would include all enterprise members except for the director, and also organizing independent unions that would represent workers as individuals in disputes with the collective or with higher administrative bodies. Thus, each half of the duality would be represented through separate institutions. Considerable progress had been made in developing these ideas, culminating in a conference at which 190 enterprises were represented that sought to codify a system of workers' control. This article argues that the crushing of this effort was a tragedy because it eliminated what would have been a highly valuable experiment in workers' control organized on a countrywide basis. Although forty‐five years have elapsed since the Warsaw Pact invasion, the problems of reconciling the tensions between individuality and collectivity, and integrating community needs with national coordination, within a functioning economy that fulfills individual, community, regional, and national requirements, remain acute.